(untitled) (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2019)
We construct sequences of definite quadrature formulae of order five which use equidistant nodes. The error constants of these quadratures are evaluated and simple a posteriori error estimates derived under the assumption that the integrand’s fifth derivative does not change its sign in the integration interval.